Neuromuscular response to exercise heat stress - Cheung, S. (Thermoregulation and human performance. Physiological and biological aspects, 2008)
Hyperthermia, through either passive exposure or exercise in hot environments, can severely impair exercise capacity, and one primary pathway of impairment may be the neuromuscular system. This is because fatigue or reduced exercise capacity in other physiological systems ultimately terminate in an inability of the muscle to adequately generate the required force to maintain a desired workload. In addition, the functional capacity of the neuromuscular system, from the central activation of the motor unit pool, through neural transmission along the peripheral nervous system, and at the individual muscle fibre, can be directly altered by elevations in local muscle and core temperature. Fatigue is a multi-modal phenomenon, so the purpose of this chapter is to survey the direct effects of heating on neuromuscular function, from the electrophysiology of isolated motor units undergoing stimulation, to isometric and dynamic contractions of isolated muscles, and through to wholebody exercise. A second objective is to briefly summarize the major methods employed by thermal and muscle physiologists to investigate muscle function, and highlight some of the limitations and challenges with current knowledge and technology.